Observations on the Effects of the Corn Laws, and of a Rise or Fall in the Price of Corn on the Agriculture and General Wealth of the Country - Malthus, T. R. (Thomas Robert), 1766-1834 (Salt Lake City, UT : Project Gutenberg, 2003)
"Observations on the Effects of the Corn Laws, and of a Rise or Fall in the Price of Corn on the Agriculture and General Wealth of the Country" by the Rev. T.R. Malthus is a scholarly examination written in the early 19th century, specifically during the Regency era. This work is primarily an economic treatise that discusses the effects of the Corn Laws on agriculture and the broader economic wellbeing of Britain. Malthus critically analyzes the implications of these laws and the fluctuations in corn prices, providing a thorough assessment relevant to policymakers of his time. In this detailed analysis, Malthus argues against the prevailing ideas of his contemporaries, particularly those put forth by Adam Smith regarding corn's unique economic position. He investigates the relationship between the prices of corn and labor, emphasizing that the impact of corn prices is not as direct as some economists claim. Malthus contends that the Corn Laws should be evaluated for their potential benefits and detriments concerning agricultural productivity and economic stability. He ultimately posits that while an independent supply of corn is commonly sought, there are significant complications and sacrifices involved in maintaining such a system. Through a balanced consideration of various economic factors, Malthus aims to guide legislative decisions regarding agricultural policy in a way that considers the broader implications for society's wealth and health. (This is an automatically generated summary.)
Release date is 2003-08-01
Produced by Charles Aldarondo. HTML version by Al Haines.
Keywords: Corn laws (Great Britain); Grain trade -- Great Britain